SUCCESSFUL SURGICAL TREATMENT OF A PATIENT WITH MULTIPLE TRUE ARTERIAL ANEURYSMS - I. P. Mikhaylov; V. L. Lemenev; G. A. Isayev; I. M. Goldina; R. S. Muslimov (Неотложная медицинская помощь)
We report a case of successful treatment of a patient with multiple aneurysms of internal carotid artery, abdominal aorta, iliac and common femoral arteries. The first stage was reconstruction of the carotid artery, and then, the second stage was resection of the abdominal aorta aneurysm and aorto-femoral bifurcation replacement.